Engineering Science and Practice : Alignment and Synergies in Curriculum Innovation : Final Report For Senior Fellowship Program. - Cameron, Ian T. (Australian Learning and Teaching Council (ALTC), 2009)
Final report of a Teaching Fellowship at The University of Queensland. A major and recurring theme in the assessment of engineering education is the abiding lack of strong linkages between theory and practice. This fellowship has focused on understanding three principal areas within modern engineering education which reflect the theory-practice partnership. First, it involves the theory-practice space in which professional engineering education occurs.